Analisis Faktor-Faktor yang Memengaruhi Penyerapan Tenaga Kerja Formal di Indonesia Tahun 2017–2024 - Devanda Widyaning Tyas; Jeane Fransina Diana Talakua (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the impact of Economic Growth, Investment, Minimum Wage, Average Years of Schooling, and Internet Access on formal labor absorption in Indonesia during the period 2017–2024. The research employs panel data combining cross-sectional data from 34 provinces in Indonesia and time series data over 8 years. The analytical method used is panel data regression. Based on model selection tests through the Chow test and Hausman test, the chosen model is the Fixed Effect Model (FEM). The results indicate that economic growth and average years of schooling have a positive and significant effect on formal labor absorption. Conversely, the minimum wage has a negative and significant effect on formal labor absorption. Investment and internet access variables do not have a significant effect on formal labor absorption. This study shows that the increase in formal labor absorption in Indonesia is more influenced by economic growth, minimum wage, and average years of schooling compared to investment or the expansion of internet access.